(untitled) (African Disability Rights Yearbook, 2021)
African states strongly embraced the adoption of the CRPD, along with its Optional Protocol. The Working Group that developed the foundational text of the treaty included delegations from seven African nations. Likewise, the lone seat allocated within the Working Group to represent national human rights institutions was held by a South African Human Rights Commissioner. Sixteen African countries signed the CRPD on the first day it opened for signature, and 34 have ratified it, contributing to a rapid entry into force. In addition, 18 African states are party to the Optional Protocol to the CRPD, thereby assenting to its complaint procedure and procedure of inquiry. The Committee on the Rights of Persons with Disabilities has included experts from the continent, and the current Special Rapporteur on Disability is South African. Also significant is the declaration by the African Union of 1999-2009 and 2010-2019 as African Decades for Persons with Disabilities. The CRPD has therefore been enthusiastically embraced on the African continent, but so too have prior human rights treaties, with uneven subsequent progress. By the same token, the CRPD challenges Africa’s states parties – as it does states parties from all regions of the world – to ensure treaty implementation in a manner that responds to broad obligations while being duly consonant to domestic social and legal norms. To foster dialogue around progressive and culturally appropriate CRPD implementation, this article begins with a brief overview of the treaty. Next, it identifies a number of CRPD provisions with particular salience for Africans with disabilities, and showcases innovative approaches, often led by disability rights advocates rather than by the obligated states, that are advancing domestic implementation of those rights on the continent. The article concludes with some thoughts regarding entry points for future CRPD advocacy that can advance implementation regionally across Africa.